The child and the childhood image into works of Joanna Papuzińska as a source of the inspiration of an early education teacher. Lost and recovered childhood - Olek-Redlarska, Zofia; Jakubowska, Emilia (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
Joanna Papuzińska is a professor at the Institute of Science Information and Library Studies of the University of Warsaw and also a writer, a poet, a literary critic, an author of anthologies. She is a frequent guest of radio programmes and an editorial worker of journals dedicated to literature for children. She is a member of numerous committees awarding prizes and a board member of the Polish Section of IBBY (The International Board on Books for Young People). She initiates conferences and meetings devoted to literature for the youngest. She is a co-originator of Książka dla dzieci foundation and the editor-in-chief of Guliwer bimonthly published since 1991 and dedicated to criticism and promotion of children’s literature. Professor Papuzińska is known for her interests in folklore and children’s subculture. She is one of the few literary critics of fantasy, also the fantasy which comes out of the child’s room. Home – space – anchor and safety has always been the most important in her works and is present in almost all her books. Joanna Papuzińska is a winner of many prizes, including the Janusz Korczak International Literary Prize. Some of her works have been translated into foreign languages: Czech, German, French, English. The works of Joanna Papuzińska are of fairy-tale character, full of warmth and kindness towards the child of early-school age. They create child’s emotional space, delight readers with sensitivity.